Real-world devOps project from start to finish. (Packt Publishing, 2023)
A DevOps project combines development and operations to streamline software delivery, emphasizing collaboration, automation, and continuous integration/deployment. It enables faster, reliable releases and efficient infrastructure management, fostering a culture of agility and innovation. The course covers a wide range of topics in the DevOps domain, including Ansible for server configuration, Docker and docker-compose for containerization, GitLab for version control and CI/CD pipelines, Let's Encrypt (certbot) for obtaining TLS certificates, WireGuard for secure VPN connections, MariaDB for database management, LXC for virtualization, iRedMail for setting up a mail server, Zulip for communication, Traefik for reverse proxy and TLS termination, Pi-hole for DNS-level ad-blocking, Nextcloud for cloud storage and collaboration, checkmk for monitoring, Borg with borgmatic for backups, and recaps of all concepts. Upon completion, we can automate server configurations, utilize containerization for efficient deployments, implement robust version control, secure connections with TLS certificates, establish secure VPN solutions, implement ad-blocking measures and cloud storage solutions, perform reliable backups, and automate essential processes independently to optimize and self-host infrastructure, streamline operations, and productivity. What You Will Learn Learn Ansible, Docker, GitLab, streamline infrastructure management Use Let's Encrypt, WireGuard to secure connections/TLS termination Explore MariaDB, iRedMail, Zulip for efficient DBs/communication Use Pi-hole, Nextcloud, checkmk for ad-blocking, storage, monitoring Explore Borg, GitLab Runner, backups for reliable data protection Automate self-hosting for optimized operations/deployments Audience This course is designed for diverse individuals and organizations, including start-ups and small companies seeking to enhance their infrastructure management practices. It is also suitable for Linux system administrators and developers who aim to transition into DevOps. Additionally, individuals interested in self-hosting their infrastructure will find this course valuable in acquiring the necessary skills and knowledge to manage their systems successfully. The prerequisites include basic Linux knowledge, domain name, VPS or physical server, and computer with macOS/Linux/Windows. About The Author Predrag Mijatovic: Predrag Mijatovic is a professionally skilled DevOps engineer with 10 years of experience. Predrag's expertise spans various domains, including system administration, DevOps engineering, and software development. He is proficient in multiple tools such as Ansible, Docker, GitLab, Jenkins, MariaDB, Nextcloud, NGINX, and Python. With his vast knowledge/practical experience, Predrag delivers an elaborate course to help students master the intricacies of DevOps. With extensive experience in system administration, DevOps engineering, and software development, Predrag Mijatovic has worked on various tools and technologies. Predrag's diverse skillsets enable him to provide insights and practical guidance across multiple platforms and environments.